2017
DOI: 10.1186/s13075-017-1311-3
|View full text |Cite
|
Sign up to set email alerts
|

HDL cholesterol efflux capacity in rheumatoid arthritis patients: contributing factors and relationship with subclinical atherosclerosis

Abstract: BackgroundLipid profiles appear to be altered in rheumatoid arthritis (RA) patients because of disease activity and inflammation. Cholesterol efflux capacity (CEC), which is the ability of high-density lipoprotein cholesterol to accept cholesterol from macrophages, has been linked not only to cardiovascular events in the general population but also to being impaired in patients with RA. The aim of this study was to establish whether CEC is related to subclinical carotid atherosclerosis in patients with RA.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 32 publications
6
51
0
Order By: Relevance
“…In addition, the fact that SSc display lower levels of total cholesterol and higher triglycerides than controls has also been previously described [10,11], although in smaller cohorts that lacked multivariate analysis. The lipid pro le differences between patients and controls found in our study are in accordance with the 'lipid paradox' [15] described in other in ammatory diseases like RA [6,16,17] or SLE [18]. This means that untreated in ammatory diseases are associated with lower levels of total cholesterol and LDL-cholesterol, and it is believed that this may stem from the lipid-lowering effects of systemic in ammation.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, the fact that SSc display lower levels of total cholesterol and higher triglycerides than controls has also been previously described [10,11], although in smaller cohorts that lacked multivariate analysis. The lipid pro le differences between patients and controls found in our study are in accordance with the 'lipid paradox' [15] described in other in ammatory diseases like RA [6,16,17] or SLE [18]. This means that untreated in ammatory diseases are associated with lower levels of total cholesterol and LDL-cholesterol, and it is believed that this may stem from the lipid-lowering effects of systemic in ammation.…”
Section: Discussionsupporting
confidence: 90%
“…In a previous report by our group including 178 RA patients and 223 sex-matched control subjects, CEC was not signi cantly different between them, although patients exhibiting higher disease activity had lower levels of CEC than patients in remission. Moreover, greater CEC was independently associated with a lower risk for the presence of carotid plaques in patients with RA [6]. Similarly, Ronda et al evaluated CEC in 30 SLE patients and 30 healthy controls [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the epidemiological data that have been used to explore the association between CEC and RA are inconsistent. Some of the previous studies have shown that the CEC is signi cantly lower in RA patients than in healthy controls, but others have failed to reach conclusions [24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 93%
“…However, the epidemiological data that have been performed to explore the association between CEC and RA was less convincing. Some of them have shown that the CEC was signi cantly reduced in RA patients compared to healthy controls, but others failed to reach the conclusions [19][20][21][22][23][24][25][26][27][28]. In 2012, Charles-schoeman et al rst reported that there was no signi cant difference in CEC among RA patients comparing to control groups, but which was inversely associated with high disease activity in RA patients [21].…”
Section: Introductionmentioning
confidence: 99%